2021
DOI: 10.4209/aaqr.210072
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Methane Condition over the South Sumatera Peatland during the COVID-19 Pandemic

Abstract: The degradation of peatlands through anthropogenic activities recently has contributed to low carbon uptake from the air. Peatlands are one of the largest sources of CH 4 (methane) emissions in terrestrial ecosystems, but during the COVID-19 pandemic with restriction policy was applied, it can affect the atmospheric CH4 concentration and change the atmospheric greenhouse gases. In Indonesia, the lockdown policy was known as the Large-Scale Social Restriction (LSSR) that was implemented in high COVID-19 case ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…They conclude that AIRS CH 4 concentrations were consistent with ground measurements of surface CH 4 concentration from the World Data Center for Greenhouse Gases (WDCGG) (R 2 = 0.83, p < 0.01) and that the AIRS CH 4 reflected the spatial and temporal variations of surface CH 4 concentrations. Rendana et al (2021) also found good agreement between AIRS and surface CH 4 measurements with an R 2 of 0.86.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…They conclude that AIRS CH 4 concentrations were consistent with ground measurements of surface CH 4 concentration from the World Data Center for Greenhouse Gases (WDCGG) (R 2 = 0.83, p < 0.01) and that the AIRS CH 4 reflected the spatial and temporal variations of surface CH 4 concentrations. Rendana et al (2021) also found good agreement between AIRS and surface CH 4 measurements with an R 2 of 0.86.…”
supporting
confidence: 59%
“…Rendana et al. (2021) also found good agreement between AIRS and surface CH 4 measurements with an R 2 of 0.86.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Page 11 of 20 Rendana et al, 2021;Stevenson et al, 2021), our analysis indicates that XCH4 concentration 233 was progressively increasing with reduced intensity over India, which might be to the reduction 234 in carbon emissions. Before the lockdown face (March 1 -March 23), the initial phase of pre-235 monsoon season, the XCH4 concentrations remain to follow the year 2019 with an increment 236 of +11 ppbv year -1 , which can be inferred from Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 72%
“…Page 5 of 20 during the COVID-19 lockdown. However, localized studies across the globe portrayed contradicting results during the lockdown (Rendana et al, 2021;You et al, 2021).…”
Section: Accepted Manuscriptmentioning
confidence: 99%